The Role of Fortified and Enriched Refined Grains in the US Dietary Pattern: A NHANES 2009–2016 Modeling Analysis to Examine Nutrient Adequacy - Papanikolaou, Yanni; Fulgoni, Victor L. III (Frontiers in Nutrition, 2021)
Background: While dietary recommendations call for greater whole-grain intake and reduced refined grain consumption, there are limited peer-reviewed studies examining the influence of fortified/enriched refined grains on nutrient adequacy. Methods: A modeling analysis using data from National Health and Nutrition Examination Survey (NHANES) 2009–2016 estimated usual daily intake of shortfall nutrients for Dietary Guidelines for Americans (DGA) in the current dietary pattern and when specific percentages of fortified/enriched refined grain foods (bread, ready-to-eat cereals, and all-grained foods) were removed from the diet (19–50-year-old adults, N = 11,169; 51–99-year-old adults, N = 9,641). Results: While American adults are currently falling short of nutrient recommendations, eliminating 25, 50, and 100% of all grains consumed in the US dietary pattern resulted in a greater percentage of adults not meeting recommendations for several shortfall nutrients, including dietary fiber, folate DFE, iron, and magnesium. Removal of all grains led to a reduced energy intake by 10% in both age groups examined. Currently, 3.8% of 19–50-year-old adults meet the adequate intake (AI) for dietary fiber. Removal of 25, 50, and 100% of grains from the diet resulted in 2.6 ± 0.3, 1.8 ± 0.2, and 0.7 ± 0.1% of adults exceeded the AI for dietary fiber, respectively. Similarly, 11.0 and 13.8% of younger and older adults, respectively, fall short of folate, DFE recommendations with the current diet. Following the removal of 100% of grains from the diet, 43.4 ± 1.1 and 56.2 ± 1.0%, respectively, were below the estimated average requirement (EAR) for folate DFE. For iron, current dietary pattern consumption shows 8.4% and 0.8% of younger and older adults, respectively, are not meeting iron recommendations, however, removal of 100% of grains from the diet results in nearly 10 and 22% falling short of the EAR. Currently, about 51 and 54% of younger and older adults are below the EAR for magnesium; however, with the removal of 100% of grains, 68 and 73%, respectively, fall below the EAR. Conclusion: Removal of specific refined grains led to an increased percentage of Americans not meeting recommendations for several shortfall nutrients, including dietary fiber, folate, iron, and magnesium.